Pengembangan Sistem Informasi Pengelolaan Tugas Akhir/ Proyek Akhir/ Skripsi pada Jurusan Teknik Elektronika FT UNP - Jonneva Verius; Ahmadul Hadi; Titi Sri Wahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The Development of Management Information Systems of Final Assignment (TA)/ Final Project (PA)/ Thesis (Skripsi)  at the Department of Electronics Engineering FT UNP aims to assist the management of TA / PA / Skripsi and provides a web-based database for TA / PA / Skripsi that already list into the Department of Electronics Engineering . During this time , the management of TA / PA / Skripsi carried out manually using a computer and can not be accessed online by the stakeholders . This system is designed to facilitate the selection of titles by KaProdi and Penasehat Akademik , guidance between lecturers and students , besides helping in the administration documentation TA / PA / Skripsi . This information system using the PHP programming language and MySQL database . This final project discusses the design method Context Diagram , DFD and ERD . System Management TA / PA / thesis can be used to manage the information from the title that has been proposed and in finalization , online tutoring , scheduling , administrative guidance and printing assignment letters online .  Keywords: Information, Management, FinalAssignment (TA) , Final Project (TA), Thesis (Skripsi), PHP, MySQL